2021
DOI: 10.1016/j.clnu.2020.10.043
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 is associated with clinically significant weight loss and risk of malnutrition, independent of hospitalisation: A post-hoc analysis of a prospective cohort study

Abstract: Background & aims Coronavirus disease 2019 (COVID-19) may associate with clinical manifestations, ranging from alterations in smell and taste to severe respiratory distress requiring intensive care, that might associate with weight loss and malnutrition. We aimed to assess the incidence of unintentional weight loss and malnutrition in COVID-19 survivors. Methods In this post-hoc analysis of a prospective observational cohort study, we enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
191
2
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(210 citation statements)
references
References 51 publications
(100 reference statements)
9
191
2
8
Order By: Relevance
“…Two studies, constituting 395 hospitalized COVID‐19 patients in total, studied malnutrition in COVID‐19 utilizing the Mini Nutritional Assessment score. They found that 42% of hospitalized patients with COVID‐19 were at risk of malnutrition and 28% of these patients were considered malnourished at the time of assessment 5,6 . Another study in 114 consecutive, hospitalized COVID‐19 patients found similar results using the Global Leadership Initiative on Malnutrition (GLIM) criteria with 42% (48/114 patients) being malnourished 7 …”
Section: Malnutrition Frequency In Covid‐19mentioning
confidence: 88%
See 2 more Smart Citations
“…Two studies, constituting 395 hospitalized COVID‐19 patients in total, studied malnutrition in COVID‐19 utilizing the Mini Nutritional Assessment score. They found that 42% of hospitalized patients with COVID‐19 were at risk of malnutrition and 28% of these patients were considered malnourished at the time of assessment 5,6 . Another study in 114 consecutive, hospitalized COVID‐19 patients found similar results using the Global Leadership Initiative on Malnutrition (GLIM) criteria with 42% (48/114 patients) being malnourished 7 …”
Section: Malnutrition Frequency In Covid‐19mentioning
confidence: 88%
“…Secondly, malnutrition is frequently seen in COVID‐19 patients 5‐7 . Disease‐associated reductions in food intake and malnutrition can contribute to tissue wasting.…”
Section: Weight Loss During Covid‐19mentioning
confidence: 99%
See 1 more Smart Citation
“…Bei Anwendung der neuen Diagnosekriterien der Global Leadership Initiative on Malnutrition (GLIM) ist bei 42–50 % der COVID-19-Patienten eine Malnutrition zu diagnostizieren [ 3 , 50 ]. In einer italienischen Studie verloren 29 % der COVID-19-Patienten während des Krankheitsverlaufs mehr als 5 % ihres Körpergewichts [ 12 ]. Ein Gewichtsverlust war dabei mit einer längeren Erkrankungs- und Hospitalisierungsdauer assoziiert [ 12 ].…”
Section: Die Rolle Der Ernährungunclassified
“…In einer italienischen Studie verloren 29 % der COVID-19-Patienten während des Krankheitsverlaufs mehr als 5 % ihres Körpergewichts [ 12 ]. Ein Gewichtsverlust war dabei mit einer längeren Erkrankungs- und Hospitalisierungsdauer assoziiert [ 12 ].…”
Section: Die Rolle Der Ernährungunclassified